Cambio de uso de suelo en el azolvamiento del embalse La Esperanza, Manabí-Ecuador - Velásquez, Francisco (2016)
The substitution of forests for other uses has had a significant impact on the silting of the reservoirs. Retrospective and prospective information was used in this investigation, with which the changes in the use of soil and the amount of sediments in the La Esperanza reservoir, during the period 1995-2015, were evaluated, direct observation techniques, surveys and treatment were applied. of satellite images (ArcGIS software version 10.2.1), by means of which the deforestation rate was determined. To calculate the production of sediments in the basin contributing to the reservoir, the universal soil loss equation (EUPS) was applied, which was complemented by bathymetry. The contrast of the variables was analyzed in the SPSS software, confirming in the graph obtained the incidence of the change of land use in the production of sediments. The results indicate that the main change in land use is that of forests for tropical agriculture; the deforestation rate in the study area was 0.091% equivalent to 733.08 ha / year and the production of sediments reached 200 Hm3. The purpose of this publication is to propose a water management tool to the organisms in charge of its management and control.